The Position of Long-Term Stimulation of the Endogenous Fibrinolytic System: Present Achievements and Clinical Perspectives - Verstraete, M (Thrombosis and Haemostasis, 1975)
There is reasonable evidence in favour of the assumption made by several investigators that patients with thrombosis of arteries or veins, or cutaneous vasculitis have, very often, a low spontaneous fibrinolytic activity. The use of long-term activators of blood fibrinolytic activity such as diguanides and anabolic steroids was shown to increase the activators to normal levels in the above mentioned and other conditions. In many instances, but not all, this induced increase of fibrinolytic activity resulted in an improved clinical condition and prevention of venous thrombosis. At the present time, there are indications that new and more powerful compounds will cause a sustained stimulation of the fibrinolytic potential and be useful for the prevention of thrombotic disorders. Some of these compounds, which have been investigated only partly at the clinical level, appear to approach the requirements of a useful oral fibrinolytic agent and it is hoped that from these observations further improvements in this range of drugs will be made.